Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

The influence of temperature and conductivity on metabolism and Per- and Polyfluoroalkyl Substance (PFAS) bioconcentration in Bluegill (Lepomis macrochirus) - Neil Fuller; Krista Kraskura; Sarah Hrynko; Michael K. Chanov; Jamie G. Suski; Youn J. Choi; Linda S. Lee; Christopher J. Salice (Ecotoxicology, 2026)
Aquatic organisms may be exposed to multiple concurrent stressors, including anthropogenic contaminants and alterations to abiotic parameters such as temperature and conductivity. Amid global climate change, elucidating the interactions between chemical and environmental factors is a priority. In recent years, per- and polyfluoroalkyl substances (PFAS) have emerged as contaminants of global concern owing to their persistence, bioaccumulation potential, and toxicity. While limited studies have documented the influence of temperature and conductivity on PFAS bioaccumulation in fish, the underlying physiological drivers associated with changes to uptake and elimination remain poorly understood. Therefore, the present study aimed to determine the influence of temperature and conductivity on metabolic parameters and bioconcentration of an environmentally relevant PFAS mixture in bluegill, Lepomis macrochirus . Fish were exposed to a mixture of perfluorooctane sulfonate (PFOS), perfluorohexane sulfonate (PFHxS), perfluorooctanoic acid (PFOA), and perfluorohexanoic acid (PFHxA) at 20 and 25 °C and conductivity levels of 300, 600, and 1200 µS/cm for a 32-day uptake and 32-day depuration period. Additionally, we measured individual resting metabolic rate (RMR), maximum metabolic rate (MMR), and aerobic scope under the same temperature and conductivity conditions. Overall, PFOS and PFHxS accumulation in the liver were consistently higher in fish at 20 °C compared to 25 °C, which was linked to more rapid contaminant elimination at higher temperatures. Resting and maximum metabolic rates increased with temperature, independent of conductivity. These results will facilitate the development of robust bioaccumulation models to enhance predictive modeling of PFAS accumulation and aid in understanding the physiological drivers of fish contaminant accumulation.

A foundation for comparative genomics and evolutionary studies in Nucella lapillus based on complete mitogenome assembly - Daniel García-Souto; Jonathan Fernández-Rodríguez; André Vidal-Capón; Neil Fuller; Juan Pizcueta; Juan J. Pasantes; Juan Galindo (Marine Biology, 2024)
The Atlantic dog whelk, Nucella lapillus , is a marine snail that exhibits divergent evolution in response to habitat adaptation, resulting in distinct populations at the phenotypic, genotypic, and karyotypic levels. In this study, we utilized short- and long-read NGS data to perform a de novo assembly of the entire mitochondrial genome of N. lapillus and developed a multiplex PCR protocol to sequence most of its length using ONT sequencing. Our analysis revealed a typical circular configuration of 16,474 bp in length with 13 protein-coding genes, 22 different tRNA genes, 2 of them showing two copies, 2 rRNA genes, and a control region. Long-read sequencing enabled us to identify a 1826 bp perfect inverted repeat within the control region. Comparative analysis of the mitogenomes of related species in the Muricidae family revealed a conserved gene configuration for N. lapillus . We found a low genetic diversity, as well as a moderate genetic differentiation among the studied populations. Interestingly, there was no observed differentiation between the two chromosomal races, suggesting either introgression and permanent incorporation of the mitochondrial DNA haplotype from one of the chromosomal races into the other or a slower evolutionary rate of the mtDNAs with respect to that of the karyotypes. Our study serves as a foundation for comparative genomics and evolutionary investigations in this species.

The Roles of Diet and Habitat Use in Pesticide Bioaccumulation by Juvenile Chinook Salmon: Insights from Stable Isotopes and Fatty Acid Biomarkers - Sara E. Anzalone; Neil W. Fuller; Kara E. Huff Hartz; Gregory W. Whitledge; Jason T. Magnuson; Daniel Schlenk; Shawn Acuña; Matt R. Whiles; Michael J. Lydy (Archives of Environmental Contamination and Toxicology, 2024)

Effect of temperature and dietary pesticide exposure on neuroendocrine and olfactory responses in juvenile Chinook salmon (Oncorhynchus tshawytscha) - Jason T. Magnuson; Neil Fuller; Victoria McGruer; Kara E. Huff Hartz; Shawn Acuña; Gregory W. Whitledge; Michael J. Lydy; Daniel Schlenk (Environmental Pollution, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Effects of dietary cypermethrin exposure on swimming performance and expression of lipid homeostatic genes in livers of juvenile Chinook salmon, Oncorhynchus tshawytscha - Neil Fuller; Jason T. Magnuson; Kara E. Huff Hartz; Corie A. Fulton; Gregory W. Whitledge; Shawn Acuña; Daniel Schlenk; Michael J. Lydy (Ecotoxicology, 2021)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)